2014
DOI: 10.1111/scs.12153
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor pedestrian fall‐related injuries among Swedish senior citizens – injuries and preventive strategies

Abstract: Senior citizens get around, to a large extent, as pedestrians, and safe walking is desirable for senior citizens allowing them to stay mobile, independent and healthy in old age. Senior citizens are over-represented in injury statistics, and fall-related injuries are common. The aim of this study was to investigate fall-related injuries including healthcare costs among senior citizen pedestrians injured when walking in public outdoor environments and to describe their self-reported causes and suggested prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 35 publications
0
32
0
2
Order By: Relevance
“…Outdoor pedestrian fall-related injuries have been a major concern for elderly people (Gyllencreutz et al 2015). Moreover, having "senior ambassadors" or a group of active seniors in a community also helps to encourage other seniors to have a more active lifestyle.…”
Section: Multilevel Analysismentioning
confidence: 99%
“…Outdoor pedestrian fall-related injuries have been a major concern for elderly people (Gyllencreutz et al 2015). Moreover, having "senior ambassadors" or a group of active seniors in a community also helps to encourage other seniors to have a more active lifestyle.…”
Section: Multilevel Analysismentioning
confidence: 99%
“…Akira et al [71] found that ice immersion, which is a method of reducing muscle spindle function, had a significant impact on the walking velocity of young adult males, suggesting a possible link between muscle spindle function and a decrement in walking ability, a well-accepted falls determinant. Additional related research suggests it is morphological changes of muscle spindles that many environmental hazards exist that increase the proclivity to falling [69,70,72,74] .…”
Section: Resultsmentioning
confidence: 99%
“…Falls and fall-related injuries represent a serious health problem worldwide, especially in regions with a cold climate [ 1 , 2 , 3 ]. In 2015, age-standardized mortality rates from accidental falls in the Nordic countries and Russia were 1.3 times higher than those for the entire World Health Organization European Region (5.2 per 100,000) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%